Intensity of Tik Tok Use and Depression with Social comparison as a Mediator Variable - sri wahyuning astuti (Analitika: Jurnal Magister Psikologi UMA, 2022)
Tik Tok users until the end of 2021 managed to touch 2 billion worldwide. Being the second most populous country to use Tik Tok, a number of problems were reported. Starting from the very high frequency of use, to issues related to the mental health of its users. The study aims to find out the relationship between Tik Tok use and Depression and the social comparisons felt by its users. The type of research used in this study is correlational quantitative. There were 108 respondents in this study collected through Google forms. The measuring instrument used to see the intensity of social media use uses the intensity scale of using Tik Tok which consists of passion, attention, duration and frequency. Meanwhile, to measure Depression using Scala Beck and the level of social comparison using the IOWA scale. The results of the data analysis show that there is a significant relationship between the use of Tik Tok and Depression with social comparisons as a mediator